The Sustainability of Public Debt and Fiscal Stability in Indonesia - Lestari Lestari; Nia Tresnawaty; Ranita Puspita Sari Dewi; Hamdalah Riziq R (Dinasti International Journal of Education Management and Social Science, 2025)
The purpose of this study is to analyse the sustainability of Indonesia's public debt under domestic and global fiscal pressures, identify macroeconomic factors that affect fiscal sustainability, and provide strategic recommendations for strengthening credible and sustainable fiscal policies. The research method used is an explanatory quantitative approach with time series data and panel data. The analysis methods used are the Generalised Method of Moments (GMM) to address endogeneity, and the Vector Error Correction Model (VECM) to measure long-term relationships. Indonesia's public debt has continued to increase in recent years, especially after the COVID-19 pandemic, raising concerns about long-term fiscal sustainability. Reliance on debt financing can narrow fiscal space and increase risks to macroeconomic stability. Therefore, it is necessary to conduct an in-depth study on the extent to which current public debt is still within sustainable limits, as well as its impact on national fiscal stability. The results of the study support the Fiscal Sustainability Theory, which asserts that fiscal sustainability is determined by the government's ability to maintain a positive primary balance and control the debt-to-GDP ratio in the long term. Empirical findings show that although Indonesia's debt ratio is still below the safe limit (60%), fiscal sustainability remains fragile if the primary deficit continues to be negative. The urgency of this research lies in sustainable fiscal policy. Increasing external pressures, such as high global interest rates and exchange rate volatility, increase the risk of government debt financing. In addition, spending allocations that are not fully productive can undermine the effectiveness of development financing. Therefore, it is important to scientifically analyse the factors that influence the sustainability of Indonesia's public debt and its impact on national fiscal stability.